2021
DOI: 10.3389/fcimb.2021.730288
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Natural Inhibitors Against SARS-CoV-2 Drugable Targets Using Molecular Docking, Molecular Dynamics Simulation, and MM-PBSA Approach

Abstract: The present study explores the SARS-CoV-2 drugable target inhibition efficacy of phytochemicals from Indian medicinal plants using molecular docking, molecular dynamics (MD) simulation, and MM-PBSA analysis. A total of 130 phytochemicals were screened against SARS-CoV-2 Spike (S)-protein, RNA-dependent RNA polymerase (RdRp), and Main protease (Mpro). Result of molecular docking showed that Isoquercetin potentially binds with the active site/protein binding site of the Spike, RdRP, and Mpro targets with a docki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 53 publications
2
34
0
Order By: Relevance
“…Thus, SASA profiles signified the conformational changes that might have happened during the protein-ligand interactions. The results obtained were in agreement with the previous studies [62] , [63] . According to the MM-PBSA free energy calculated between RdRp and the ligands, the binding free energy (ΔG bind) of RdRp-Fidaxomicin (—334.2±16.7 kj/mol) was stronger than that of RdRp-Rifabutin (—326.5±13.6 kj/mol), which was in line with the results of docking and MD simulation.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Thus, SASA profiles signified the conformational changes that might have happened during the protein-ligand interactions. The results obtained were in agreement with the previous studies [62] , [63] . According to the MM-PBSA free energy calculated between RdRp and the ligands, the binding free energy (ΔG bind) of RdRp-Fidaxomicin (—334.2±16.7 kj/mol) was stronger than that of RdRp-Rifabutin (—326.5±13.6 kj/mol), which was in line with the results of docking and MD simulation.…”
Section: Resultssupporting
confidence: 93%
“…12 ). Previous docking and simulation studies of RdRp with various inhibitors including natural compounds have showed similar amino acids that are in agreement with the findings of the present study [63] , [64] .
Fig.
…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…As shown in Table 1, EGCG and Isoquercetin were effective to inhibit SARS-CoV-2 replication by 50% at 85.65 ± 6.45 mM and 23.99 ± 1.07 mM, respectively. Isoquercetin has already shown its effectiveness against Influenza and Ebola virus (16,50) and has been proposed for SARS-CoV-2 treatment (51,52). Although the EC 50 of EGCG was relatively high using this assay, it was previously described as effective to block infection of ancestral SARS-CoV-2 and UK-B.1.1.7, SA-B.1.351 and CA-B.1.429 variants, in vitro (53).…”
Section: Inhibition Effects Of Remdesivir Egcg and Isoquercetin Again...mentioning
confidence: 92%
“…In addition, a proof of concept was provided by a study by Kushwaha et al, showing the docking of key SARS-CoV-2 proteins to quercetin (51). Their findings revealed that quercetin is a capable drug molecule.…”
Section: Quercetinmentioning
confidence: 97%